2007
DOI: 10.1088/0031-9155/52/24/004
|View full text |Cite
|
Sign up to set email alerts
|

Hard tissue ablation with a spray-assisted mid-IR laser

Abstract: The objective of this study was to understand the dominant mechanism(s) for dental enamel ablation with the application of water spray. A free-running Er,Cr:YSGG (yttrium, scandium, gallium, garnet) laser was used to ablate human enamel tissue at various radiant exposures. During dental ablation, distilled water was sprayed on the sample surface, and these results were compared to ablation without a spray (dry ablation). In order to identify dominant ablation mechanisms, transient acoustic waves were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…These findings mirror investigations using the laser with spray in dental ablation, which demonstrated that ablation of bone with spray resulted in relatively clean edges without thermal damage while more charring and peripheral cracks were observed in dry ablation. [17][18][19] Our results are in accord with the observations of others, as there was reduced charring and carbonization on surfaces with saline drops, although the ablation depth/rate was not noticeably different. The craters were observed to be irregular in shape, being more of a parabolic cone shape as opposed to the almost perfect squares and circles that were produced by the fs systems.…”
Section: Use Of Erbium:yag Laser In Bonesupporting
confidence: 92%
“…These findings mirror investigations using the laser with spray in dental ablation, which demonstrated that ablation of bone with spray resulted in relatively clean edges without thermal damage while more charring and peripheral cracks were observed in dry ablation. [17][18][19] Our results are in accord with the observations of others, as there was reduced charring and carbonization on surfaces with saline drops, although the ablation depth/rate was not noticeably different. The craters were observed to be irregular in shape, being more of a parabolic cone shape as opposed to the almost perfect squares and circles that were produced by the fs systems.…”
Section: Use Of Erbium:yag Laser In Bonesupporting
confidence: 92%
“…In the case of hard tissue ablation, temperature elevation between 44 and 47 o C may lead to bony tissue necrosis 10 . Compared to non-spray case, the spray application exhibited no thermal injury by cooling the tissue with water, during the laser irradiation the lager craters due to strong pressure emission of water vaporization 11 . By applying water layer on tissue, the desired ablation result depends on both water layer thickness and incident radiant exposure; the geometry of the crater presented a more regular and clean shapes 12 The application of a perfluorocarbon layer removed lager ablation volume than water layer and dry 13 .…”
Section: Introductionmentioning
confidence: 94%
“…The non-contact mode of laser beam offers arbitrary intricate and more precise cut geometry; aseptic effects can be expected by some special laser systems [2][3][4] .As we know that during laser ablation on the surface of hard tissue leads to thermal damage to surrounding tissue 5 . A number of studies presented that the additional water Hight -speed camera applied to target tissue surface not only makes it possible to reduce the thermal stress and prevent damage [6][7][8][9] ,but also serves to increase the ablation rate and efficiency, improve surface morphology [10][11] . Different investigators have performed several methods to find out the influence of additional water on the hard tissue ablation process, the primary mechanism reported for laser-water interaction is cavitation effect which included vapor channel and cavitation bubble 12 .…”
Section: Introductionmentioning
confidence: 99%